Um estudo sobre sistema de informações gerenciais como apoio à gestão educacional de cursos de graduação - Pavoni, Valter (Universidade do Vale do Rio dos Sinos, 2018)
Brazilian Education has had a new configuration due to the expansion of the private educational sector since the 1990’s. In this context, educational management of the undergraduate courses, through the figure of the coordinator, has been a key element in the management process as it guarantees academic excellence and sustainability of Brazil’s higher education institutions. In order to enhance the process of decision taking among the coordinators of undergraduate programs and also to contribute to the quality and sustainability of those courses, this research has the general aim of proposing a System of Managerial Information (SIG, for short in Portuguese), based on both internal and external data. The research seeks to answer the following question: in the management of the undergraduate courses of Higher Education Institutions, what pieces of information are relevant to the courses managers when quality and sustainability are taken into consideration? The institution that has been empirically used was Universidade do Vale do Rio dos Sinos, a jesuit and community university in Southern Brazil. A case study has been carried out as the method for this research, with both a quantitative and qualitative approach. As instruments for the data collection, we have used interviews with managers of the Undergraduation Department as well as an online questionnaire to courses managers. For the data analysis, the technique of descriptive analysis has been used. The final result of this project lets show the difficulty and effort of coordinators and managers to search and access information which is necessary for their managerial activities. Furthermore, it was possible to classify several types of information regarding its importance and accessibility for college managers aiming at the development of a system of managerial information for undergraduate programs managers. It has also been possible, by means of a prototype, the simulation of the system based on the IT architecture that was proposed for this project.
Keywords: Sistemas de informações gerenciais; Práticas da gestão educacional; Coordenador de curso de graduação; Arquitetura de tecnologia de informação; Managerial information systems; Educational management practices; Undergraduate program manager; Information technology architecture; ACCNPQ::Ciências Humanas::Educação